A Double Isotope Technique for Estimating Insulin Degradation in Vivo - Ritzl, F.; Feinendegen, L. E.; Schnippering, H. G. (Nuklearmedizin - NuclearMedicine, 1974)
1) A double isotope technique is described which permits measuring by external counting the catabolism of insulin in the human liver. 131I-insulin is used together with 51Cr-insulin as internal standard. Following catabolism of the labeled insulins 131I migrates into the iodine pool of the body whereas 51Cr remains at the site of insulin breakdown. Therefore, site and rate of insulin catabolism can be recognized from the change in the isotopic ratio 131I/51Cr.2) In the livers of 3 normal individuals, insulin half-lives of 58, 95, and 92.5 minutes were measured. In 3 patients with sub-clinical diabetes mellitus, insulin half-lives were 124.5 minutes, 127 minutes, and 99.5 minutes. One patient with clinical diabetes showed an insulin half-life of only 47.8 minutes; a second patient with clinical diabetes mellitus due to autoimmune response leading to large amounts of insulin antibody in his peripheral blood, showed an insulin half-life greatly prolonged to 972 minutes.3) The 51Cr-labeled insulin was indistinguishable from 125I-labeled insulin in the immunoassay, in molecular size, in diffusion rate in tissues, absorption to subcellular particles, and rate of hydrolysis in liver homogenates in vitro.